Ecological Evaluation of Sponge City Landscape Design Based on Aquatic Plants Application - Dan Jiang; Rui Hua; Jian Shao (Land, 2022)
Urbanization increases the impervious surface of land and disrupts the hydrological cycle of urban water resources. Optimum landscape design based on climatic and geographical factors can reduce the destructive effects of urban development on surface and subsurface flows. The construction of a sponge city is an essential step towards achieving this structure. Aquatic plants are the most important component of the ecological regeneration of urban landscapes. The land cover changes caused by aquatic plants reduce the speed of water and increase the penetration of runoff into the porous environment. In addition, not only can the use of aquatic plants as the main component of water saving for ecological restoration control water erosion, but it can also have a positive effect on landscape architecture. Therefore, the aim of this study was to develop a multi-objective urban landscape design model based on the use of aquatic plants. Moreover, the limitations of improving the urban ecosystem with aquatic plants were analyzed based on the theory of ecological restoration in a sponge city. The required area for the cultivation of these plants was calculated according to the flood return periods and the two objective functions of land slope and runoff rate. The results show that surface runoff decreased by 15% and that rainfall and flood decreased by 21% for a 50-year return period.